PHONOLOGICAL LOOP PHENOMENA ON QUR’AN RECITERS “BADDELEY’S MODEL OF VERBAL WORKING MEMORY” - Hurriyati, Evi Afifah; Fitriana, Efi; Cahyadi, Surya; Srisayekti, Wilis (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
This study aimed to explore how the process occurs in the working memory to memorize and keep memorizing the Qur’an. Also, to explore how the phenomenon of verbal working memory of phonological loop on the Qur’an reciter and the factors that affect working memory capacity. There were 48 students (25 female and 23 male) and 4 teachers (1 female and 3 male) of two Tahfidzinstitution in Bogor, West Java, Indonesia, who participated in this study. The study used survey and interview techniques to explore four characteristics of verbal working memory phonological loop: (1) word length effects, (2) articulatory suppression, (3) the irrelevant speech effect, and (4) the phonological similarity effect. Qur'an memorizing is significant with working memory concept that is involving phonological loop. Individual has different response to the phonological loop phenomenon because they have differences in working memory capacity